The effect of teams games tournament assisted by Quizizz paper mode on motivation and biology learning outcomes - Ingka Liantri; Shefa Dwijayanti Ramadani; Weni Anggraini (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2024)
Motivation as a critical factor in supporting academic achievement is well-established. However, efforts to enhance student motivation and improve learning outcomes remain a significant challenge. This research aims to analyze the effect of using the Teams Games Tournament (TGT) learning model assisted by Quizizz Paper Mode (Q-Cards) on motivation and cognitive learning outcomes of class XI students at SMA IT Ihsanul Fikri Mungkid on the immune system material. The research design was quantitative quasi-experimental with a non-equivalent control group pretest-posttest design. The research results showed a significant influence of the Teams Games Tournament (TGT) learning model assisted by Quizizz Paper Mode (Q-Cards) on learning motivation with a significance value of 0.000 and student learning outcomes with a significance value of 0.000. The results of this research can be used as input for teachers and prospective teachers in considering the appropriate models and media to increase student motivation and learning outcomes to improve the quality of education and as a reference base for further research related to student motivation and cognitive learning outcomes.Abstrak. Peran motivasi sebagai faktor penting dalam mendukung prestasi akademik sudah diketahui dengan baik. Namun, upaya untuk meningkatkan motivasi siswa dan meningkatkan hasil belajar masih menjadi tantangan yang signifikan. Tujuan penelitian ini adalah untuk menganalisis pengaruh penggunaan model pembelajaran Teams Games Tournament (TGT) berbantuan Quizizz Paper Mode (Q-Cards) terhadap motivasi dan hasil belajar kognitif siswa kelas XI SMA IT Ihsanul Fikri Mungkid pada materi sistem imunitas. Desain penelitian yang digunakan adalah quasi eksperimen kuantitatif dengan non-equivalent control group pretest-posttest design. Hasil penelitian menunjukkan bahwa terdapat pengaruh yang signifikan model pembelajaran Teams Games Tournament (TGT) berbantuan Quizizz Paper Mode (Q-Cards) terhadap motivasi belajar dengan nilai signifikansi 0,000 dan hasil belajar siswa dengan nilai signifikansi 0,000. Hasil penelitian ini dapat dijadikan masukan bagi guru dan calon guru dalam mempertimbangkan model dan media yang tepat untuk meningkatkan motivasi dan hasil belajar siswa guna meningkatkan mutu pendidikan dan sebagai bahan acuan untuk penelitian selanjutnya terkait motivasi dan hasil belajar kognitif siswa.